Standardized Pathology Report for Colorectal Cancer, 2nd Edition - Baek-hui Kim; Joon Mee Kim; Gyeong Hoon Kang; Hee Jin Chang; Dong Wook Kang; Jung Ho Kim; Jeong Mo Bae; An Na Seo; Ho Sung Park; Yun Kyung Kang; Kyung-Hwa Lee; Mee Yon Cho; et al. (Journal of Pathology and Translational Medicine, 2020)
The first edition of the ‘Standardized Pathology Report for Colorectal Cancer,’ which was developed by the Gastrointestinal Pathology Study Group (GIP) of the Korean Society of Pathologists, was published 13 years ago. Meanwhile, there have been many changes in the pathologic diagnosis of colorectal cancer (CRC), pathologic findings included in the pathology report, and immunohistochemical and molecular pathology required for the diagnosis and treatment of colorectal cancer. In order to reflect these changes, we (GIP) decided to make the second edition of the report. The purpose of this standardized pathology report is to provide a practical protocol for Korean pathologists, which could help diagnose and treat CRC patients. This report consists of “standard data elements” and “conditional data elements.” Basic pathologic findings and parts necessary for prognostication of CRC patients are classified as “standard data elements,” while other prognostic factors and factors related to adjuvant therapy are classified as “conditional data elements” so that each institution could select the contents according to the characteristics of the institution. The Korean version is also provided separately so that Korean pathologists can easily understand and use this report. We hope that this report will be helpful in the daily practice of CRC diagnosis.